Design and 3D printing of reconfigurable structures - Teo, Ee Hian (Nanyang Technological University, 2021)
Reconfigurable structures canchange after fabricating, this feature of reconfiguration have greaterapplication potential in engineering in the future as it can change its form and structure accordingly to suit and address different needs in engineering. The structure is made up of single modular units being repeatedly fixed together, this leads to the structure to isolate single modular units that are damaged, allowing it to be easily pin-pointed and replaced by fabricating another similar single unit, this cut cost as the structure can be salvaged by replacing a single unit instead of the whole structure.